Linguistic Features of English for Science and Technology - Olusegun Oladele Jegede (Britain International for Academic Research (BIAR) Publisher, 2020)
The goal of the study was to examine the linguistic features of English for Science and technology. To achieve the goal, content analytical method was adopted. This method was chosen because the sources of data for the study were two texts, one on science and the other on technology. The linguistic features of the contents of the texts were identified and categorised; the relevance of the linguistic features in the selected texts was determined; and the roles the linguistic features played in driving home the messages of science and technology texts were discussed. The findings revealed that texts for science and technology employ different levels of linguistic analysis such as graphology, lexis, syntax to drive home their messages. The study also found that the meaning and messages of the contents of science and technology texts rely heavily on these linguistic features. Thus, linguistic features are very relevant, and perform vital roles n the construction of science and technology texts. The study concluded that the adept employment of linguistic features gives scientific and technological writings sound logic, accurate thoughts, and descriptive expressions.